A Meta-Analysis of the Impact of the Flipped Classroom Learning Model on Students' Motivation in Physics Education - Hudaa, Perdana Miftachul; Fatmaryanti, Siska Desy (Buletin Edukasi Indonesia, 2025)
The Flipped Classroom learning model is an innovative educational approach with the potential to enhance students' learning motivation. This study aims to synthesize research findings on the impact of the Flipped Classroom model on students' motivation. A meta-analysis was conducted using seven research studies, focusing on the educational levels and calculating effect sizes with Microsoft Excel 2010. The results reveal that the highest effect size was observed at the higher education level, while the lowest effect size was also noted in the same category, suggesting variability within this level. Overall, the findings indicate that the Flipped Classroom model positively influences students' learning motivation. Further empirical research is recommended to validate and strengthen the results of this preliminary meta-analysis.